Girl on a wire - Bond, Gwenda (Skyscape, 2014)
Two rival circus families, the Maronis and the Garcias, compete for the spotlight in the new "Cirque American" circus show. Sixteen-year-old Jules Maroni wants to be a high-wire walker like her father, and once she gets the chance she skyrockets to fame as the girl in the red tutu. Then she finds a peacock feather on her dress--an emblem of bad luck--sending her for help in the most unlikely of places--Remy Garcia, son of her family's rivals.